A Novel Framework for Understanding the Pattern Identification of Traditional Asian Medicine From the Machine Learning Perspective - Bae, Hyojin; Lee, Sanghun; Lee, Choong-yeol; Kim, Chang-Eop (Frontiers in Medicine, 2022)
Pattern identification (PI), a distinctive diagnostic system of traditional Asian medicine, is an act of inferring the pathological nature or the location of lesions from observed symptoms. Despite its great importance in theory and practice, principles of information processing in PI systems are generally unclear. Here, we present a novel framework to understand the PI system from the machine learning perspective. After a brief introduction to the dimensionality of the data, we propose that the PI system can be modeled as a dimensionality reduction process and suggest analytical issues that can be addressed by applying our framework. Our framework provides a novel way of thinking and contributes to expanding the scope of inquiry, adopting powerful mathematical tools, and enriching explanatory theory in traditional Asian medicine.